1975
DOI: 10.1021/ja00851a008
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy and quantum chemical analysis of some N-nitrosamines

Abstract: carbonyl compounds by H atom donors may be of the same order.The chemistry of the triplet state of sym-triazine has been studied34 and was found to be similar to that of the diazabenzenes examined in this work.Abstract: Photoelectron (PES) and electronic absorption spectra of a series of N-nitrosamines have been obtained and compared with the results of C N D 0 / 2 and C N D O / S calculations; all observable PES and electronic absorption bands have been assigned. The highest occupied molecular orbital is a A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…Nauman and co-workers obtained photoelectron and electronic absorption spectral data for a series of nitrosamines . The charge densities of the NNO moieties obtained from their theoretical calculations (CNDO/2 and CNDO/S) revealed an electronegative O-atom, an electropositive nitroso N-atom, and a slightly electronegative amine N-atom; they also proposed an involvement and redistribution of the molecules' σ electrons.…”
Section: Spectroscopy and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Nauman and co-workers obtained photoelectron and electronic absorption spectral data for a series of nitrosamines . The charge densities of the NNO moieties obtained from their theoretical calculations (CNDO/2 and CNDO/S) revealed an electronegative O-atom, an electropositive nitroso N-atom, and a slightly electronegative amine N-atom; they also proposed an involvement and redistribution of the molecules' σ electrons.…”
Section: Spectroscopy and Structurementioning
confidence: 99%
“…The charge densities of the NNO moieties obtained from their theoretical calculations (CNDO/2 and CNDO/S) revealed an electronegative O-atom, an electropositive nitroso N-atom, and a slightly electronegative amine N-atom; they also proposed an involvement and redistribution of the molecules' σ electrons. Thus, they suggested that the dipolar resonance form in eq 43 should be classified as the limiting case for the π-electron system; they calculated that the HOMO of R 2 NNO is the nitroso π-orbital, with the second HOMO being an n orbital localized mostly on the O-atom. ,343b Wang and co-workers measured the HeI photoelectron spectra of the nitrosamines R 2 NNO (R = Me, Et, n -Pr), performed ab initio SCF MO calculations (631*G basis sets), and suggested that the HOMO of R 2 NNO is π in nature and largely localized in the NO group , The infrared spectra of aliphatic nitrosamines display bands in the 1425−1460 and 1030−1150 cm -1 ranges due to υ NO and υ NN , respectively .…”
Section: Spectroscopy and Structurementioning
confidence: 99%
“…The total charges on the atoms for conformation S are given in Table 111, following the usual Mulliken population analysis [57], together with the computed dipole moment p. The alternation of charge found for many polar molecules [44] is observed from 0 3 to N1 but the present calculations predict the carbon atoms to be negative, in contrast to the semiempirical results [32].…”
Section: A Dimeth Ylnitrosaminementioning
confidence: 91%
“…There have been several studies of the photo-electron spectra, both x-ray PES [31,34] and uv PES [32,33] which have established the first few ionization potentials, but there has been disagreement as to the nature and symmetry of the highest occupied orbitals [31,33].…”
Section: 6mentioning
confidence: 99%
“…The composite structure of these bands has been analyzed using deconvolution techniques. The partial p and d densities of states in Cul have been determined (271). ESCA has been used to investigate the valence bands of the silver halides; assignments of the photoemission peaks are made using a point charge electrostatic model (272).…”
Section: Satellite Linesmentioning
confidence: 99%